2023
DOI: 10.3390/molecules28155670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Variation of the Differential Coloring Substances in Rapeseed Petals with Different Colors Using UPLC-HESI-MS/MS

Abstract: Rapeseed’s (Brassica napus L.) colorful petals have important ornamental values. However, the mechanisms of regulating petals coloration in rapeseed are still unknown. In our study, we investigated the key differential coloring substances in nine rapeseed cultivars with different petal colors, and 543 metabolites were detected and characterized through UPLC-HESI-MS/MS. Among them, the kinds and contents of flavonols, flavones, and anthocyanidins were the main contributors to petals’ coloration. Tamarixetin-, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The flavonoid pathway is also involved in the formation of petal color [ 18 , 24 , 42 ], and it was reported that the flavonols, flavones, and anthocyanidins were the main contributors to petal coloration [ 42 ]. A KEGG functional annotation and RT-qPCR analysis revealed that the expression of BnaA10g23330D ( BnF3′H ) could affect the synthesis of downstream peonidin and delphinidin in B. napus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid pathway is also involved in the formation of petal color [ 18 , 24 , 42 ], and it was reported that the flavonols, flavones, and anthocyanidins were the main contributors to petal coloration [ 42 ]. A KEGG functional annotation and RT-qPCR analysis revealed that the expression of BnaA10g23330D ( BnF3′H ) could affect the synthesis of downstream peonidin and delphinidin in B. napus [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flower color of rape petals is generally yellow or milky white [4]. In the last few years, rapeseed breeding experts have bred a series of rapeseed varieties with different colors, such as wine red, deep red, deep purple, light purple, bright yellow, light yellow, milky white, pure white, orange red and so on, through artificial breeding, close hybridization, mutation breeding and genetic engineering [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The flower color of rape petals is generally yellow or milky white [4]. In the last few years, rapeseed breeding experts have bred a series of rapeseed varieties with different colors, such as wine red, deep red, deep purple, light purple, bright yellow, light yellow, milky white, pure white, orange red and so on, through artificial breeding, close hybridization, mutation breeding and genetic engineering [5,6].Flower color is mainly determined by the type and content of pigments, while anthocyanins are mainly determined by plant pigments in petals [7,8]. Plant pigments are mainly divided into four categories, including phenolic pigments (represented by flavonoids), pyrrole derivative pigment (represented by chlorophyll), ketones and quinone derivatives pigments (represented by alkaloids), and terpenoid pigments (represented by carotenoids, etc.)…”
mentioning
confidence: 99%
“…For example, epicatechin, quercetin, isorhamnetin derivatives, and cyanidin derivatives were found to be the main pigment components of red rapeseed petals, while kaempferol derivatives were found to be mainly distributed in yellow and white petals, as identified by ultra-high-performance liquid chromatography–HESI–mass spectrometry (UPLC-HESI-MS/MS) [ 5 ]. However, other researchers found that the main components of red rapeseed are glycosylated anthocyanins (peonidin-3-O-glucoside, cyanidin-3-O-galactoside, and cyanidin-3-O-glucoside) and kaempferol derivatives [ 6 ]. One possible reason for this difference is the different study materials used by researchers, as the color definition of “red” is not consistent.…”
Section: Introductionmentioning
confidence: 99%